Angiotensinogen and C3 compete for renin-induced complement activation - Kristoffersson, Ann-Charlotte; Sköld, Albin; Welinder, Charlotte; Wendler, Markus; Kalliokoski, Gabriella; Bekassy, Zivile; Karpman, Diana (Frontiers in Immunology, 2025)
Renin from plasma, kidney, and recombinant sources was previously demonstrated to cleave C3 to C3a and C3b. C3a was generated at a similar rate to that by C3 convertase, and C3 cleavage was inhibited by the renin inhibitor aliskiren. Renin endogenously produced by Calu6 cells also led to C3 deposition on cells. These results have been challenged by another group suggesting that recombinant renin does not cleave C3 or that renin was contaminated by trypsin, which also cleaves C3. Here, we investigated C3 cleavage by recombinant renin and competitive inhibition in the presence of angiotensinogen. Recombinant renin was analyzed by mass spectrometry using endopeptidase LysC digestion and did not contain trypsin. C3 cleavage, using our protocol and that of the other group, showed cleavage to C3b by immunoblotting. Cleavage was inhibited by aliskiren, which inhibits renin but not trypsin. Cleavage to C3a occurred within 1 min as detected by enzyme-linked immunosorbent assay (ELISA). Angiotensinogen competed for renin-mediated C3 cleavage and inhibited C3a generation, but C3 did not inhibit cleavage of angiotensinogen to angiotensin I (detected by ELISA). The results suggest that renin cleaves C3 but angiotensinogen is its preferred substrate. The interaction between renin and C3 may gain importance in the kidney where renin concentrations are considerably higher than in the circulation and when the primary substrate, angiotensinogen, is cleaved and thereby depleted.